Die unheimliche Nummer Sechs - Eine Entscheidung zum Ausgleich grenzüberschreitender Konzernverluste - Stefan Homburg (Internationales Steuerrecht, 2010)
The article considers a judgement of the fiscal court of Lower Saxony regarding cross-border group losses.
Keywords: H25; 330; Group taxation; Marks & Spencer; Konzernbesteuerung